Deferoxamine-conjugated AgInS2nanoparticles as new nanodrug for synergistic therapy for hepatocellular carcinoma - Isara Phiwchai (2018)
© 2017 Elsevier B.V. Herein, a new nanodrug that exhibits multi-therapeutic modalities for synergistic treatment of hepatocellular carcinoma is reported. The nanodrug is composed of carboxymethyl cellulose modified silver indium sulfide nanoparticle (CMC-AgInS 2 NP, served as a source of reactive oxygen species) covalently linked with deferoxamine (DFO, served as iron chelating agent). The DFO/CMC-AgInS 2 nanodrug was taken up by the HepG2 cell and accumulated within the cytosol as well as the nucleus, leading to induction of cell arrest in the G2/M phase and subsequent apoptosis cell death. Compared to DFO, the DFO/CMC-AgInS 2 nanodrug demonstrated better anti-proliferative activity against the HepG2 cell. As they were cultured in a medium supplemented with ferric ions, the HepG2 cells were induced to grow faster as compared to the cells without the addition of ferric ions. Fortunately, our nanodrug was found to inhibit the cell growth induced by ferric ions. Our results indicate that the nanodrug has synergistic effect for treatment of HepG2 cells via the intrinsic therapeutic property of CMC-AgInS 2 NP and the iron chelating capability of DFO.